Emotional Intelligence and Job Satisfaction as Predictors of Organizational Citizenship Behavior - Muhammad Rizki; Dila Fitriani; Daeylen Beby; Nurul Utami; Rifqah Salsabila (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Organizational citizenship behavior (OCB) of health workers is very important in improving the effectiveness and efficiency of services in health centers in a region. However, the reality in the health centers in the region shows that not all health workers consistently show strong OCB. This study also aims to determine whether there is an influence of emotional intelligence and job satisfaction on the OCB of health workers in the health centers in the region. This study uses a quantitative methodology. Primary data were then collected through the use of a questionnaire instrument. The population of this study consisted of 60 health workers working in the health centers in the region. The total sampling technique was also used because the population was below 100; as a result, the sample size for this study was 60. The findings of this study indicate a significant positive influence of emotional intelligence on OCB. Furthermore, job satisfaction was also found to have several significant positive influences on OCB. In the end, emotional intelligence and job satisfaction simultaneously showed a significant positive influence on OCB.